2017
DOI: 10.14260/jemds/2017/33
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ventriculoperitoneal Shunt Surgery Through Conventional and Ventriculoscopic Technique

Abstract: BACKGROUNDAims & Objective-To compare the position of ventricular end between conventional and Ventriculoscope guided technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Our finding is consistent with a study by Hermann 25 and also with another study of the coauthor. 26 But to recommend the routine use navigation system for the insertion shunt, we need a multicentric study with large sample size. Ambekar et al 27 and Kamat et al 28 showed in their study that patients with increased protein levels in CSF are at a high risk of VP shunt blockage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding is consistent with a study by Hermann 25 and also with another study of the coauthor. 26 But to recommend the routine use navigation system for the insertion shunt, we need a multicentric study with large sample size. Ambekar et al 27 and Kamat et al 28 showed in their study that patients with increased protein levels in CSF are at a high risk of VP shunt blockage.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding is consistent with a study by Hermann 25 and also with another study of the coauthor. 26 But to recommend the routine use navigation system for the insertion shunt, we need a multicentric study with large sample size.…”
Section: Discussionmentioning
confidence: 99%